Farmers’ Perception of Integrated Pest Management and its Impact on Cucumber Production in Bangladesh - Rahman, Md. Sadique; Harun-Ar-Rashid, M. (Journal of the Bangladesh Agricultural University, 2020)
IPM is an ecosystem-based strategy that focuses on long-term prevention of pests or their damage through a combination of techniques such as biological control, habitat manipulation, modification of cultural practices, and use of resistant varieties. Farmers’ perception of integrated pest management (IPM) and its impact on cucumber (Cucumis sativus L.) production were assessed in Bangladesh using few econometric models. A total of 119 cucumber farmers were interviewed in 2015 to achieve the objectives. Most of farmers perceived that IPM was beneficial for farmers’ health, water bodies. IPM adoption significantly reduced the pesticide applications cost per hectare (P<0.01), while increasing the net return (P<0.10) from cucumber cultivation. The adoption of IPM also had a significant and positive impact (P<0.01) on the level of technical efficiency of the adopters. The production of cucumber could be increased to a larger extent by improving technical efficiency of the growers. Trainings and demonstration programmes to improve the knowledge and technical skills of farmers are essential. However, findings of this study cannot be generalized, as this was administered on a small number of cucumber farmers. A large-scale survey may be useful in developing a complete scenario for the adoption of IPM in Bangladesh. J Bangladesh Agril Univ 18(3): 674–679, 2020 https://doi.org/10.5455/JBAU.58830